PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS PERMAINAN MONOPOLI DI ERA NEW NORMAL - Siti Istiningsih; Darmiany Darmiany; Fitri Puji Astria; Muhammad Erfan (COLLASE (Creative of Learning Students Elementary Education), 2021)
During learning from home activities, students spend more time at home and the most common activity is playing. In the new normal era, students are used to playing so they need additional time to focus on teaching and learning activities. One of the efforts that can be made by educators in overcoming this problem is to develop a game that involves educational content that can make students more active. Therefore, this study aims to develop a monopoly game-based learning media with the aim that students become more active in participating in teaching and learning activities. This research is a development research and the development model used is ADDIE which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. Data analysis was carried out qualitatively. The results of the development show that the monopoly game-based learning media is feasible and effective to be used as a learning medium as the validation results from media experts who get a percentage of 81%, validation results by material experts with a percentage of 86%, and the responses of students in small groups who obtain a percentage of 85%.